Service accommodation for visiting lecturers at the International Islamic University Malaysia: an analytical maqasid study - Mohd Salleh, Hamzah; Zakariyah, Luqman; Abd Hadi, Asman (2018)
The Sharīʿah is deemed characterized by its comprehensiveness, completeness, and the benefits it provides for people in any time or place. The establishment of hospitality services is a goal of the Sharīʿah because it brings maṣlaḥah (benefit) to all involved as it also depicts the value and virtue Islam upholds. The International Islamic University Malaysia (IIUM) is amongst the most important education institutions which considered operating in the light of the Sharīʿah. The study of hospitality towards international lecturers in IIUM is important in determining the extent of compliance of IIUM to the Maqāṣid al-Sharīʿah (goals of the Sharīʿah). This paper aims to identify the position of Islamic jurisprudence in hospitality and determine the parameter of Maqāṣid al-Sharīʿah in hospitality. It examines the extent of realization of the concept of Maqāṣid al-Sharīʿah through hospitality services provided for international staffs in IIUM. The study includes several vantage points such as receiving the international staff from the Airport; provision of accommodation for them prior their arrival. The paper uses random sampling to interview some lecturers on the way they perceived IIUM hospitality services towards them at their arrival and before they settled down in the society. The result has shown that IIUm has successful in compliance with the Maqāṣid al-Sharīʿah in some areas of hospitality especially I receiving new staff from the airport and accommodating them in hotel for certain period, however, some areas need to be improved.